Cultural Recontestation of Chinese Ethnicity in Surakarta City During the Reformation Era - Alam, M. Bagus Sekar; Rudiansyah; Lianisyah, Ulfah Yanuar; Sugiarti, Tati (Universitas Airlangga, 2024)
One of the assimilation policy implementations during the New Order era was prohibiting the display of Chinese traditions and culture in public. This discriminatory policy ended in the Abdurahman Wahid Presidential era, marked by the revocation of Presidential Instruction No. 14 of 1967 through Presidential Decree No. 6 of 2000. The Chinese community regained the rights to publicly practice their religion, traditions and culture. This study investigates the forms of Surakarta Chinese community’s cultural recontestation after this revocation. This study uses historical method. Primary sources include archives of Inpres No. 14 of 1967 and no. 26 of 1998, Kepres No.6 of 2000 and interview data. The results show that after the revocation of Inpres No. 14 of 1967, the Surakarta Chinese community regained the freedom to practice their religion, traditions, and culture in public, such as praying at the temple, holding Grebeg Sudiro Festival during the Chinese New Year, revitalizing Balong Chinatown village while maintaining typical Chinese architecture, increasing the number of temples, and making Kalipepe River Bandar in Balong Chinatown village as a tourist destination. This study concludes that the Chinese community in the reformation era has regained their space for cultural contestation in public.